Longitudinal measurement invariance of the meaning in life questionnaire in Chinese college students - Luo, Jie; Tang, Fu-Chuan; Yang, Ren; Gong, Jie; Yao, Cheng-Kui; Huang, Xinquan; Chen, Wei; Zhao, Shuo-Ying (Frontiers in Psychology, 2022)
The Meaning in Life Questionnaire (MLQ) is a popular tool to measure the presence of and one’s search for meaning in life. Although the validity of the MLQ has been verified in previous studies, the evidence from longitudinal measurement invariance (LMI) of the MLQ is still lacking. The current study aimed to examine the LMI of the MLQ in a sample of Chinese college students (N = 328) at a one-year interval. Multigroup confirmatory factor analysis (MCFA) was used to examine the LMI of the MLQ over four time points (over the course of one year). Results indicate that the MLQ has strict longitudinal invariance across one-year in Chinese college students, and the latent means difference of MLQ-P is not significant differences across time, while the latent means difference of MLQ-S show significant differences between Time 1 and the other time points. Moreover, the internal consistency reliabilities (e.g., alpha and omega) of the MLQ scores were acceptable at all four time points, and the stability coefficients across time were moderate. These findings provide preliminary evidence that the MLQ has satisfactory longitudinal properties in Chinese college students.